TLC profiling and antioxidant activity of phenolic compound from Sterculia oblongata bark extract - TRI MURNINGSIH; PRAPTIWI PRAPTIWI; LIANA LIANA; AHMAD FATHONI (Smujo International, 2019)
Abstract. Murningsih T, Praptiwi, Liana, Fathoni A. 2019. TLC profiling and antioxidant activity of phenolic compound from Sterculia oblongata bark extract. Nusantara Bioscience 11: 44-48. In the present study, we investigated the total phenolic content and in- vitro antioxidant activity of Sterculia oblongata. Total phenolic content (TPC) of the methanol extract was examined by Folin-Ciocalteu reagent and gallic acid as standard. The in-vitro antioxidant activity was performed by DPPH free radical scavenging activity and ?-carotene bleaching assay. The result showed that the TPC of methanol extract was the highest (P<0.05) compared to other extracts. There is a positive and significantly very high Pearson’s correlation between antioxidant activity index (AAI) and TPC (r = 0.996). A negative and significantly high Pearson’s correlation was obtained between IC50 value and TPC (r = -0.885). The result of ?-carotene bleaching assay showed that the rate of the decreased antioxidant activity of S.oblongata extract was lower than that of ?-carotene/linoleic acid. The results suggest that the extract of S. oblongata can be used as a natural antioxidant. However, further investigation to isolate and identify the chemical compounds responsible for antioxidant was needed